Gyvūnų maloniniai epitetai tautosakoje - Jasiūnaitė, Birutė (Vilnius University Open Series, 2022)
This paper deals with derivational and semantic problems of diminutive epithets of animals. Such words are usually used in Lithuanian folk songs for domestic or wild animals, first of all, for a horse and a hare. They have been produced with nine different diminutive suffixes, most popular among them were -elis and -ėlis. In most cases diminutive epithets of animals have been produced from suffixal derivatives or compound words (jautelis baubuolėlis, gegutytė pilkuolytė, kurmelis žemrausėlis, ančiukai raibaplunksnėliai). The most common motivation features of such words was the color of the animal (kiškelis baltužėlis, žirgelis sartonėlis), its body parts (ožkutė rudakutė, zuikelis statausėlis), its typical actions (katinėlis repečkėlis, laputė čiuženutė).
Keywords: gyvūno maloninis epitetas; deminutyvas; mažybinė priesaga; žodžių daryba